2002
DOI: 10.1038/sj.onc.1205706
|View full text |Cite
|
Sign up to set email alerts
|

Re-expression of hSNF5/INI1/BAF47 in pediatric tumor cells leads to G1arrest associated with induction of p16ink4a and activation of RB

Abstract: Truncating mutations and homozygous deletions in the hSNF5/INI1/BAF47 subunit of human SWI/SNF complexes occur in most malignant rhabdoid tumors and some other malignancies. How loss of hSNF5 contributes to tumorigenesis remains unknown. Because the SWI/ SNF subunit BRG1 is required for RB-mediated cell cycle arrest, we hypothesized that hSNF5 deficiency disrupts RB signaling. Here we demonstrate that unlike BRG1, hSNF5 deficient cells retain functional RB since ectopic expression of either p16ink4a or a const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
176
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(192 citation statements)
references
References 83 publications
(105 reference statements)
15
176
1
Order By: Relevance
“…The p16/CCND1/CDK4/RB/E2F pathway inactivation has been initially reported as the prominent downstream effect of SMARCB1 inactivation in MRTs (20,30,36). However, more recently, engineered mouse models showed that SMARCB1 haploinsufficiency cooperates with both RB and TP53 haploinsufficiency to increase penetrance and reduce latency of tumor onset (9,22,37) and in vitro studies showed that SMARCB1 inactivation globally affects the epigenetic status of the cancer genome (38,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The p16/CCND1/CDK4/RB/E2F pathway inactivation has been initially reported as the prominent downstream effect of SMARCB1 inactivation in MRTs (20,30,36). However, more recently, engineered mouse models showed that SMARCB1 haploinsufficiency cooperates with both RB and TP53 haploinsufficiency to increase penetrance and reduce latency of tumor onset (9,22,37) and in vitro studies showed that SMARCB1 inactivation globally affects the epigenetic status of the cancer genome (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that VAESBJ represents a unique model to investigate the role of SMARCB1 inactivation in the context of epithelioid sarcoma. Because in MRTs cells, SMARCB1 tumor suppressor activity has been shown to impinge on cell proliferation (29,30), apoptosis (31), senescence (20,27), and cell motility (21), we investigated these phenotypes in SMARCB1-deleted VAESBJ epithelioid sarcoma cell line. Here, we provide evidence that SMARCB1 restoration in this cell line affects cell proliferation, enhances the sensitivity to genotoxic stress, and reduces cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several groups have documented that hSNF5/INI1 re-expression in MRT cell lines leads to the accumulation of cells in the G 0 /G 1 phase of the cell-cycle (Betz et al, 2002;Versteege et al, 2002;Zhang et al, 2002). This hSNF5/INI1-induced cell-cycle arrest requires a functional RB/E2F pathway and is reversible (Medjkane et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Re-expression of BRG1 in the BRG1-deficient cancer cell lines restores RB function, repressing E2F targets, such as cyclin E (Hendricks et al, 2004). Although SNF5 is dispensable for RB-induced cell-cycle arrest, re-expression of SNF5 into malignant rhabdoid tumor cell lines leads to G1 cell-cycle arrest, possibly through p16 INK4a induction and Cyclin D1 repression (Betz et al, 2002;Zhang et al, 2002). Furthermore, several reports suggest that ablation of p53 dramatically accelerates tumor formation caused by Snf5 deficiency (Isakoff et al, 2005;Klochendler-Yeivin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%